2015
DOI: 10.3390/rs70201758
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Satellite Rainfall Estimates for Drought and Flood Monitoring in Mozambique

Abstract: Satellite derived rainfall products are useful for drought and flood early warning and overcome the problem of sparse, unevenly distributed and erratic rain gauge observations, provided their accuracy is well known. Mozambique is highly vulnerable to extreme weather events such as major droughts and floods and thus, an understanding of the strengths and weaknesses of different rainfall products is valuable. Three dekadal (10-day) gridded satellite rainfall products (TAMSAT African Rainfall Climatology And Time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
279
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(303 citation statements)
references
References 31 publications
14
279
1
9
Order By: Relevance
“…TRMM data, in situ measurements and other atmospheric and climatology models were assimilated in [66] to create an ensemble precipitation product Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS, University of California Santa Barbara -Climate Hazards Group, Santa Barbara, California, U.S.) with a superior resolution at 0.05° × 0.05°. Precipitation from CHIRPS performed well statistically for flood and drought monitoring, particularly for meteorological complex regions [67]. The current study combines TRMM7.0 and CHIRPS2.0 rainfall products.…”
Section: Precipitationmentioning
confidence: 99%
“…TRMM data, in situ measurements and other atmospheric and climatology models were assimilated in [66] to create an ensemble precipitation product Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS, University of California Santa Barbara -Climate Hazards Group, Santa Barbara, California, U.S.) with a superior resolution at 0.05° × 0.05°. Precipitation from CHIRPS performed well statistically for flood and drought monitoring, particularly for meteorological complex regions [67]. The current study combines TRMM7.0 and CHIRPS2.0 rainfall products.…”
Section: Precipitationmentioning
confidence: 99%
“…Nevertheless, the performance varies among the rainfall products because of different data sources and retrieving algorithms (Derin & Yilmaz, 2014;Toté et al, 2015). In addition, the 4 performance also varies for the same data type across different regions and seasons (Gebremichael et al, 2014;Hu et al, 2014).…”
mentioning
confidence: 99%
“…Variations of topography can significantly compromise the interpolation of observed rainfall (Thiemig et al, 2012). The rainfall stations are also sparsely and unevenly 14 distributed over the basin, which can be a source of systematic errors when interpolating aerial rainfall (Dembélé & Zwart, 2016;Toté et al, 2015).…”
mentioning
confidence: 99%
“…The CCD-derived estimates are then merged with World Meteorological Organization's Global Telecommunication System (GTS) gauged data using a 'smart interpolation' approach . Comparisons with other satellite precipitation estimates and observed rainguage data have shown that this data set provides useful long-term precipitation estimates for Africa (Ceccherini et al, 2015;Dembélé and Zwart, 2016;Toté et al, 2015). In addition, this dataset has been used in the East Africa region 15 previously to provide high resolution and combined gauge-satellite precipitation estimates (Ayana et al, 2016;Pricope et al, 2013).…”
Section: Climate Datamentioning
confidence: 97%